Misidentification of Acute Psychiatric Symptoms in the Emergency Room: Clinical Experience in China - Liu, Fang; Chen, Jianjun; Du, Yang; Jiang, Wenxia; Gong, Lei; Mu, Jun (Frontiers in Psychiatry, 2021)
Introduction: Patients who come to the emergency department because of acute psychiatric symptoms are often not admitted to the correct department timely. The purpose of this study is to identify the clinical characteristics of patients with acute psychiatric symptoms in order to achieve early and correct triage in the emergency room. Methodology: We conducted a cross-analysis of in-patients who first came to the emergency department with acute psychiatric symptoms and then admitted to the department of neurology or psychiatry between years 2012 and 2018. Among them, 70 patients were re-diagnosed and re-transferred, with 38 patients to the department of neurology and 32 patients to the department of psychiatry. The clinical characteristics, laboratory examination, and Neuropsychiatric Inventory were analyzed. Results: Patients who were re-diagnosed with neurological diseases were more prone to have somatic symptoms (headache, dizziness) (P < 0.05). Due to the atypical early clinical manifestations in the emergency room, fever and positive neurological signs do not necessarily represent the diagnosis of neurological diseases. On the other hand, the absence of these manifestations does not guarantee the diagnosis of psychiatric illness. According to Neuropsychiatric Inventory(NPI), abnormal behaviors, changes in appetite, and sleep disturbances were more obvious in patients with neurological diseases (P < 0.05). While patients with psychiatric disorders often showed prominent irritability (P < 0.05). Conclusions: Acute psychiatric symptoms are usually complex and diverse. The triage and diagnosisshould be based on multiple factors. After triage, clinical symptoms should be dynamically observed. Keywords: Acute psychiatric symptoms, Misidentification, Differential diagnosis, Clinical characteristics, Emergency room